2012
DOI: 10.1038/aps.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-based virtual screening and density functional theory approach to identifying novel butyrylcholinesterase inhibitors

Abstract: Aim: To identify the critical chemical features, with reliable geometric constraints, that contributes to the inhibition of butyrylcholinesterase (BChE) function. Methods: Ligand-based pharmacophore modeling was used to identify the critical chemical features of BChE inhibitors. The generated pharmacophore model was validated using various techniques, such as Fischer's randomization method, test set, and decoy set. The best pharmacophore model was used as a query in virtual screening to identify novel scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 49 publications
2
41
0
1
Order By: Relevance
“…The moderately active and inactive compounds exhibited high energy gaps that were not suitable for the reactivity of the molecules. Our results were consistent with published research in the literature [19,28,29] . Thus, the DFT results indicated that the hit compounds have equivalent or greater electronic properties than most of the active compounds.…”
Section: Density Functional Theorysupporting
confidence: 94%
See 3 more Smart Citations
“…The moderately active and inactive compounds exhibited high energy gaps that were not suitable for the reactivity of the molecules. Our results were consistent with published research in the literature [19,28,29] . Thus, the DFT results indicated that the hit compounds have equivalent or greater electronic properties than most of the active compounds.…”
Section: Density Functional Theorysupporting
confidence: 94%
“…Similarly, the compounds of the test set were also classified based on their activities. The 2D chemical structures of all compounds were drawn using ChemSketch [19] and were subsequently exported to Discovery Studio v3.5 (DS) for the generation of their corresponding 3D structures.…”
Section: Selection Of Compounds and Dataset Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanto los organofosforados como los carbamatos inhiben las dos colinesterasas, que tienen similitudes en su estructura, pero localizaciones y funciones distintas [13,14]. Según el sustrato sobre el que actúan y su inhibidor, son clasificadas en dos subfamilias: las acetilcolinesterasas o colinesterasas verdaderas presentes en sistema nervioso central y periférico, músculo y eritrocitos [13]; y las butirilcolinesterasas, conocidas también como pseudocolinesterasas o colinesterasas plasmáticas producidas en hígado y secretadas en el plasma, que además se hallan en músculo liso y adipocitos [6,14,13].…”
Section: Discussionunclassified